Piano Sonata no. 2 in A major, op. 2, no. 2, published by Arnold - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; F. W. Arnold; Elberfeld, 2024)
Piano Sonata no. 2 in A major op. 2, no. 2, reprint by F. W. Arnold of the edition published by J. André, with plate number removed.